The Second Forbidden Beta Transition of Cobalt 60 - Alam, Rashida (My University, 1963)
The 1.481 Mev second forbidden beta transition from the ground state of cobalt 60 to nickel 60 has been reinvestigated using the Siegbahn type spectrometer and discussed in this thesis. The end point energy, intensity and log ft values of the transition have been measured.
In addition, internal conversion peaks of two weak gamma transitions in nickel 60 have been observed. The experiment to find the energy and intensities of these transitions are described.
Keywords: Physics; Physics